Plant–Soil Feedbacks and Temporal Dynamics of Plant Diversity–Productivity Relationships. (July 2021) - Thakur, Madhav P.; van der Putten, Wim H.; Wilschut, Rutger A.; Veen, G.F. (Ciska); Kardol, Paul; van Ruijven, Jasper; Allan, Eric; Roscher, Christiane; van Kleunen, Mark; Bezemer, T. Martijn
Abstract : Plant–soil feedback (PSF) and diversity–productivity relationships are important research fields to study drivers and consequences of changes in plant biodiversity. While studies suggest that positive plant diversity–productivity relationships can be explained by variation in PSF in diverse plant communities, key questions on their temporal relationships remain. Here, we discuss three processes that change PSF over time in diverse plant communities, and their effects on temporal dynamics of diversity–productivity relationships: spatial redistribution and changes in dominance of plant species; phenotypic shifts in plant traits; and dilution of soil pathogens and increase in soil mutualists. Disentangling these processes in plant diversity experiments will yield new insights into how plant diversity–productivity relationships change over time. Highlights: Plant diversity–productivity relationships often become stronger over time, but we know little about what biotic mechanisms may drive temporal dynamics of diversity–productivity relationships. Recent advances in plant-soil feedback (PSF) research can help gain new mechanistic insights into temporal dynamics of diversity–productivity relationships. We suggest three processes driving temporal changes in PSF of individual plants in diverse plant communities: spatial redistribution and changes in the dominance of plant species; phenotypic shifts in plant traits; and dilution of soil pathogens and increase in soil mutualists. These three processes reduce the strength of negative feedback in the absence of external disturbances and make diverse plant communities more productive over time.